Zoomorphic motifs on early Islamic scratch-engraved glass from Alexandria: a case study - Renata Kucharczyk (Polish Archaeology in the Mediterranean, 2022)
The two pieces of scratch-engraved glass presented in this article, one with lion and the other with camel imagery, are to date the only examples of animal representations executed in this technique that are known from the archaeological excavation of the Kom el-Dikka site in Alexandria (Egypt). As such, they contribute significantly to the still very small assemblage of scratch-engraved glass with zoomorphic themes from the Islamic world, so far made up of altogether no more than seven fragments, including these two. The shards come from cylindrical cups, a popular form in use in the Early Islamic period, dated to the 8th–9th centuries.